Foursquare and identity: Checking-in and presenting the self through location. (June 2017) - Saker, Michael
Foursquare is a location-based social network (LBSN) that allows people to share their location with friends by 'checking-in' at a given place using their smartphone. The application can also access the location-based recommendations left by other users. Drawing on original qualitative research with a range of Foursquare users, the article sets out to examine this LBSN and its impact on identity in three ways. Using Schwartz and Halegoua's 'spatial self' as 'a theoretical framework encapsulating the process of online self-presentation based on the display of offline physical activities', the article first examines the extent to which users understand check-ins as mediating identity. Second, the article explores whether the act of using Foursquare beyond the sharing of location can similarly be seen as contributing to identity. Last, the article examines what effect location-based recommendations might be having on how users subsequently experience themselves.